Putative Markers of Adulteration in Olive Oil: Prospects and Limitations - Garcia, Raquel (2014)
Authentication is becoming an issue of increasing relevance in olive oil and is generally motivated by economic benefits. Blending of extra virgin olive oil (EVOO) with refined olive oil (ROO) constitutes one of the most common types of adulteration of this top grade product. Concerning this particular topic, the most recent attempts of several research groups on the finding of some target compounds as markers of adulteration of EVOO with ROO will be reviewed. All efforts developed until now to find markers of adulteration in blends of EVOO with ROO have contributed to increase the knowledge about this topic although it is mandatory to exploit new compounds that could be assigned as reliable adulteration markers able to detect with high selectivity, sensitivity and accuracy this fraudulent practice.